Word of mouth, digital media, and open innovation at the agricultural SMEs - Tutur Wicaksono; Agus Dwi Nugroho; Zoltán Lakner; Anna Dunay; Csaba Bálint Illés (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Small and medium enterprises (SMEs) must continue to combine technology and market adaptation or open innovation to sustain their business. One of these ways is to promote their products and services extensively. This study investigated the best media to promote SMEs in the local agricultural markets of Hungary. This study uses an approach of asking consumers where they receive information about SMEs and their determinants. Research questionnaires were distributed to 156 consumers who purchased agricultural products on the Budapest Central Market Hall. The data were analyzed using a binary logistic model. The studies showed that consumers obtain market information through word-of-mouth and digital media. Older consumers tend to receive information through word-of-mouth, while consumers who rarely interact with others or who are educated or foreign choose digital media. Therefore, SMEs in Hungary's local agricultural markets have yet to focus on developing promotional activities through these two media. For the future, recommendations are given to SMEs in Hungary to maintain the quality of products and services and to develop two-way communication in digital media (e-WOM).
Keywords: 650; education; age; information; markets; nationality; social interaction